Efforts to Increase the Number of Visits to the Cirebon Mask Museum - Devita, Zeffanya; Wibowo, Toni Ari; Hernawati, Yuke (Jurnal Toursci, 2025)
Background. Cirebon City is a cultural city. The city of Cirebon has just inaugurated a new museum, the Mask Museum, located on Jalan Siliwangi, which was built using cultural heritage from the City Hall. Purpose. This research is essential to increase the number of visits to the Cirebon Mask Museum. Method. This study examines the efforts made by Museum managers to increase the Number of Visits to the Mask Museum using a qualitative research method with a non-probability sampling approach, with data collected through interviews, observation, and documentation, and data analysis using descriptive and SWOT analyses. Conclusion. Based on interviews with managers, the theory of the Tourism Marketing Mix indicates that digital and non-digital promotions within the government's scope are very effective in increasing the number of visits. Implementation. The government collaborates with non-governmental parties to promote the museum.